Determinant of Firm Performance Two Different Approaches - Soehadi, Aguis W. (Forum Manajemen; Vol 13 No 68 (1999): Forum Manajemen Prasetiya Mulya | November 1999, 1999)
The question of what determines firm peiformance still defies a definite answer. The problem is extremely complex, because there are a vast number of influences on peiformance. There are two major paradigms in determining firm peiformance. One is based on industrial organisation economic field that was developed earlier by Mason-Bain. This concept suggests that market structure variables (environment) influence strategy and in tum, affect the firm peiformance. The other line of paradigm builds on strategic management field, which was developed earlier by Nourse-Doury. They viewed that firms{ peiformances were not de-· termined simply at the mercy of industry factors but dominantly by firm{s specific factors.